Hubungan Kemampuan Metakognitif dengan Gaya Belajar Siswa - Kusumawati, Nyimas Inda; Antari, Luvi; Supriadi, Agus; Febriana, Dyah (Universitas Muhammadiyah Palembang, 2025)
Metacognitive ability and learning style are two crucial aspects that influence the success of students learning processes. Although they differ conceptually, both are interrelated and interact in determining learning effectiveness. This study aims to explore the relationship between metacognitive ability and learning style, as well as to evaluate whether metacognitive ability corresponds proportionally with learning style. The method used in this research is literature analysis. By collecting and analyzing various relevant studies, the researcher investigates the relationship between metacognitive ability and learning style, both conceptually and practically. The analysis results reveal a positive correlation between metacognitive ability and learning style. Students with higher metacognitive ability tend to be more aware of their own learning styles and are more effective in managing learning strategies according to their preferences. However, the relationship between the two is complex, as it is also influenced by other factors such as prior learning experiences, motivation levels, and the surrounding learning environment. In conclusion, metacognitive ability plays a significant role in helping students understand and optimize their respective learning styles. Nevertheless, although metacognitive ability may assist in understanding and applying students’ learning styles, the relationship between the two is not always linear or proportional. Therefore, a holistic understanding of the student learning process requires an in-depth comprehension of both aspects.